1956
DOI: 10.1111/j.1476-5381.1956.tb01077.x
|View full text |Cite
|
Sign up to set email alerts
|

Trypanocidal Action of Phenanthridine Compounds: Further 2:7‐diamino Phenanthridinium Compounds

Abstract: Woolfe (1952) showed that the trypanocidal activity of dimidium bromide (2: 7-diamino-10-methyl-9-phenyl-phenanthridinium bromide; I) was influenced by changing the quaternary group, and later (Woolfe, 1956) (Woolfe, 1952) were used, and drugs were given in single doses subcutaneously to mice. The Median Curative Dose (CD5O) was estimated as the dose necessary to remove parasites from the peripheral blood of 50% of infected mice for a period of not less than one month. Active drugs were compared with dimidium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1962
1962
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…Flow cytometric method for measuring the percentage of apoptotic nuclei after propidium iodide staining in hypotonic buffer proves useful for assessing apoptosis of specific cell populations in heterogeneous tissues such as bone marrow, thymus and lymph nodes [ 26 ]. But propidium iodide was confirmed that has acute toxicity on mouse (LD 16 mg/kg) [ 27 ]. The toxicity of PI makes this method cannot detect the survival rate at multiple time points for the acute toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometric method for measuring the percentage of apoptotic nuclei after propidium iodide staining in hypotonic buffer proves useful for assessing apoptosis of specific cell populations in heterogeneous tissues such as bone marrow, thymus and lymph nodes [ 26 ]. But propidium iodide was confirmed that has acute toxicity on mouse (LD 16 mg/kg) [ 27 ]. The toxicity of PI makes this method cannot detect the survival rate at multiple time points for the acute toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been assumed that the inhibition of nucleic acid synthesis by the drug ethidium bromide (EtdBr) (Fig. 1) is due to an intercalative mode of binding (1)(2)(3)(4)(5)(6)(7)(8). High-resolution nuclear magnetic resonance (NMR) studies have shown that ethidium binds to a single site in yeast phenylalanine tRNA (tRNAPhe) as well as unfractionated tRNAs, and this site has been interpreted as involving intercalation between the amino acid stem base pairs U6-A67 (AU6) and U7-A66 (AU7) (9).…”
mentioning
confidence: 99%
“…22 A fenantridina é usada como esqueleto base para a sintese de vários compostos, semelhantes mas com eficiências diferentes no tratamento de infestações por tripanossomos. Woolfe 23 demonstrou em seu trabalho que a eficiência dos compostos sintetizados é alterada de acordo com os grupos que ocupam a posição do sal de amônio quaternário. Na Figura 1 pode-se observar as estruturas do esqueleto base da fenantridina(a) e do brometo de etídio(b).…”
Section: -O Brometo De Etídio (Be)unclassified